To the Question of the Origin of the Piano Sonata in Uzbekistan - Sidikova Aliya Maratovna (Researchparks Publishing, 2021)
The piano sonate has repeatedly become the subject of studies of scientists from different countries. It was analyzed in detail the genre peculiarity of the sonata, its style and composite features found at different historical stages of development. Scientists largely attracted the shaped world of the Sonata of composers of the past and present as an extensive sphere of emotional and spiritual and intellectual embodiment of their own ideas, thoughts and feelings. In the history of modern piano literature, Sonata genre takes a relatively modest place. Few of the composers of the late XX - the beginning of the XXI century regularly refers to this genre and has a large number of Sonate in his